Association of monocarboxylate transporter-1 (MCT1) A1470T polymorphism (rs1049434) with forward football player status - Massidda, M.; Mendez-Villanueva, A.; Gineviciene, V.; Proia, P.; Drozdovska, S. B.; Dosenko, V.; Scorcu, M.; Stula, A.; Sawczuk, M.; Cieszczyk, P.; Calò, C. M. (International Journal of Sports Medicine, 2018)
The aim of this study was to investigate the association between the MCT1 (monocarboxylate transporter 1) A1470T polymorphism and positional roles in a large cohort of professional football players from five different countries. We compared genotype distributions of the MCT1 A1470T polymorphism between football players (n=694) and non-athlete controls (n=781) from Italy, Poland, Lithuania, Ukraine and Malta, and we analyzed the MCT1 genotype distributions with respect to the players` positions in the field (e. g. forwards, midfielders, defenders and goalkeepers). Genomic DNA was extracted from either buccal epithelium or peripheral blood using a standard protocol. In the pooled cohort of Italian, Polish, Lithuanian and Ukrainian football players, forwards (n=148) were more likely than controls (n=781) to possess the A allele ( 2=7.067, p=0.029, FDR q value 0.116), with a greater likelihood of having the AA genotype compared with the TT genotype (OR=1.97; C.I.=1.07-3.64; p=0.021, FDR q value 0.086). The MCT1 AA genotype was significantly more frequent in forwards then in controls. Further studies are needed to confirm these findings in other professional football player cohorts.